Introduction to Creative Economy for Early Childhood in Beurandeh Village: Building a Creative and Independent Generation - Saputra, Irwan; Miswar, Edy; Kusuma, Teuku Meldi; Umuri, Khairil; Nabilah, Nabilah; Fajri, Muhammad Iqbal (Universitas Syiah Kuala, 2024)
Themed community service activities aim to introduce the basic concepts of creative economy to young children. This activity was implemented with interactive learning methods involving stories, games, and creative activities, such as making crafts and painting. The active participation of 20 children aged 5 to 8 years old showed high enthusiasm, which contributed to the improvement of children's understanding of creative economy concepts and practical skills. The results of the activity showed a significant increase in understanding and skills, with the percentage of basic understanding increasing from 70% to 85% and practical skills from 60% to 80%. In addition, this activity also succeeded in fostering children's independence and creativity, which is expected to be a provision for a more creative and innovative generation in the future. The main challenges in implementing this activity are the limited props and the lack of understanding of parents about the importance of the creative economy at an early age. The long-term impact of this activity is expected to improve community welfare through the development of an independent and innovative creative generation.